2012
DOI: 10.1371/journal.pone.0045826
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin (NGAL) Predicts Response to Neoadjuvant Chemotherapy and Clinical Outcome in Primary Human Breast Cancer

Abstract: In our previous work we showed that NGAL, a protein involved in the regulation of proliferation and differentiation, is overexpressed in human breast cancer (BC) and predicts poor prognosis. In neoadjuvant chemotherapy (NACT) pathological complete response (pCR) is a predictor for outcome. The aim of this study was to evaluate NGAL as a predictor of response to NACT and to validate NGAL as a prognostic factor for clinical outcome in patients with primary BC. Immunohistochemistry was performed on tissue microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 43 publications
(55 reference statements)
1
42
0
Order By: Relevance
“…In mouse models of colorectal cancer, LCN2 expression was associated with reduced metastasis 45 although, paradoxically, it was also associated with the decreased overall survival of patients with colorectal cancer 46 . Nevertheless, recent results suggest that LCN2 expression is associated with shorter disease-free survival 47 and is an independent prognostic factor for decreased disease-free survival in primary human breast cancer 48 ; LCN2 is also associated with a poor prognosis in hepatocellular carcinoma 36 .…”
Section: Intracellular Iron Regulation Is Modified In Cancermentioning
confidence: 99%
“…In mouse models of colorectal cancer, LCN2 expression was associated with reduced metastasis 45 although, paradoxically, it was also associated with the decreased overall survival of patients with colorectal cancer 46 . Nevertheless, recent results suggest that LCN2 expression is associated with shorter disease-free survival 47 and is an independent prognostic factor for decreased disease-free survival in primary human breast cancer 48 ; LCN2 is also associated with a poor prognosis in hepatocellular carcinoma 36 .…”
Section: Intracellular Iron Regulation Is Modified In Cancermentioning
confidence: 99%
“…In addition, the tumor microenvironment may alter NF-kappaB activity [66]. Many transcription factors, including the estrogen and androgen receptors, regulate NGAL expression by both positive and negative mechanisms [67][68][69][70][71][72][73][74][75][76][77]. 11 NGAL is an important molecule in many different types of cancer including: breast [9,10,77], colorectal (CRC) [78,79], endometrial [80], esophageal [7,81], gastric cancer [6], liver [82][83][84], lung [85][86][87] ovarian [88], pancreatic [89,90], prostate [76,91], renal [8,92] and thyroid cancer [68].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…NGAL has also been observed in breast and other cancers and may be a predictor of poor patient survival and response to chemotherapy [72][73][74]94,96,97,105]. Breast cancer progression has been shown to be promoted by NGAL [96].…”
Section: Ngal and Breast Cancermentioning
confidence: 99%
“…LCN2, a small molecular weight secreted glycoprotein, is up-regulated in a variety of cancers, including ESCC [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Recent studies suggest LCN2 is a key player in different cancer types [10,12,23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LCN2 can tightly bind to bacterial siderophore through a cell surface receptor, possibly serving as a potent bacteriostatic agent by sequestering iron, regulating innate immunity and protecting kidney epithelial cells from ischemia-reperfusion injury [5][6][7]. Elevated LCN2 has also been observed in a wide spectrum of solid tumor cells, including breast [8][9], colorectal [10][11], pancreatic [12], ovarian [13], thyroid [14], bladder [15], kidney [16] and gastric cancers [17], and gliomas [18], as well as esophageal squamous cell carcinomas (ESCC) [19][20][21]. We previously found that LCN2 is overexpressed in gastric carcinoma and its induction by 12-o-tetradecanoylphorbol-13-acetate (TPA) is controlled by CCAAT/enhancer-binding protein beta (C/EBPβ) [17].…”
Section: Introductionmentioning
confidence: 99%